2013
DOI: 10.1128/aac.00162-13
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Formyl-Methionyl Transferase Mutants Demonstrate Reduced Virulence Factor Production and Pathogenicity

Abstract: Inhibitors of peptide deformylase (PDF) represent a new class of antibacterial agents with a novel mechanism of action. Mutations that inactivate formyl methionyl transferase (FMT), the enzyme that formylates initiator methionyl-tRNA, lead to an alternative initiation of protein synthesis that does not require deformylation and are the predominant cause of resistance to PDF inhibitors in Staphylococcus aureus. Here, we report that loss-of-function mutations in FMT impart pleiotropic effects that include a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…Therefore, although resistance to GSK1322322 can occur through mutations in the FMT protein in S. pyogenes and even S. pneumoniae, the mutations are associated with severe in vitro fitness costs, and it can be anticipated that the mutants would not be able to subsist under more challenging in vivo conditions. In addition, although the loss of FMT function in S. aureus does not seem to have a pronounced fitness cost in vitro, recent studies have demonstrated that FMT mutants are nonhemolytic and cannot cause productive infections in animal models (20). Mutations in the PDF protein, in contrast, could be expected to yield fitter stable mutants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, although resistance to GSK1322322 can occur through mutations in the FMT protein in S. pyogenes and even S. pneumoniae, the mutations are associated with severe in vitro fitness costs, and it can be anticipated that the mutants would not be able to subsist under more challenging in vivo conditions. In addition, although the loss of FMT function in S. aureus does not seem to have a pronounced fitness cost in vitro, recent studies have demonstrated that FMT mutants are nonhemolytic and cannot cause productive infections in animal models (20). Mutations in the PDF protein, in contrast, could be expected to yield fitter stable mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Plates were incubated at 35°C, and growth and resistance were evaluated at 24 and 48 h. In cases in which a large number of mutants were obtained, only a representative set of colonies was tested. In the cases of S. aureus and S. pyogenes, colonies were also analyzed for production of hemolysin in blood agar plates, as it is known that S. aureus fmt mutants are nonhemolytic (20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations